1998
DOI: 10.1111/j.1547-5069.1998.tb01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Chronic Illness

Abstract: Spirituality has evolved beyond religious considerations to encompass multidimensional and existential perspectives that are integral to maintaining well-being for the chronically ill. A deeper understanding of spirituality enhances the potential for nurses to identify spiritual needs and incorporate spiritual caring into practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 55 publications
1
29
0
2
Order By: Relevance
“…Extensive studies have shown the importance of diet and exercise on health, particularly for heart conditions; and stress management, improved interpersonal relationships, and enhanced spirituality have been shown to be effective for treating a variety of medical conditions including arthritis, pain, headache, cancer symptoms, hypertension, and insomnia. 12,24,25 This study has several limitations. First, this is an open study with no control group in which all subjects received the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown the importance of diet and exercise on health, particularly for heart conditions; and stress management, improved interpersonal relationships, and enhanced spirituality have been shown to be effective for treating a variety of medical conditions including arthritis, pain, headache, cancer symptoms, hypertension, and insomnia. 12,24,25 This study has several limitations. First, this is an open study with no control group in which all subjects received the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…56 When distinctions have been made, there has been tremendous variability across studies with respect to the definitions that have been used. Studies have conceived of spirituality as a focus on God or other power that guides the universe, faith in mystical or transcendental experiences, and/or adherence to certain moral values and belief about relationships with people and a higher power.…”
Section: Identified Themesmentioning
confidence: 99%
“…This discussion will be informed by recent definitions that posit 'meaning-making' and 'experience as a person' as the starting point for the exploratory research on spirituality [1,4,12,16,24,26,33,34,35]. Concisely stated, 'spirituality is defined as that part of the self where the search for meaning takes place' [34]: it is 'the organising centre of people's lives' [12].…”
Section: Introductionmentioning
confidence: 99%